Rising star the making of Barack Obama - Garrow, David J. 1953- (William Morrow, an imprint of Harper Collins Publishers, 2017)
Obama's speech at the 2004 Democratic National Convention instantly catapulted him into the national spotlight and led to his election four years later as America's first African-American president. Garrow has created a vivid portrait that reveals not only the people and forces that shaped the future president but also the ways in which he used those influences to serve his larger aspirations